8x+5x+3=x-4+7

Simple and best practice solution for 8x+5x+3=x-4+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+5x+3=x-4+7 equation:


Simplifying
8x + 5x + 3 = x + -4 + 7

Reorder the terms:
3 + 8x + 5x = x + -4 + 7

Combine like terms: 8x + 5x = 13x
3 + 13x = x + -4 + 7

Reorder the terms:
3 + 13x = -4 + 7 + x

Combine like terms: -4 + 7 = 3
3 + 13x = 3 + x

Add '-3' to each side of the equation.
3 + -3 + 13x = 3 + -3 + x

Combine like terms: 3 + -3 = 0
0 + 13x = 3 + -3 + x
13x = 3 + -3 + x

Combine like terms: 3 + -3 = 0
13x = 0 + x
13x = x

Solving
13x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
13x + -1x = x + -1x

Combine like terms: 13x + -1x = 12x
12x = x + -1x

Combine like terms: x + -1x = 0
12x = 0

Divide each side by '12'.
x = 0

Simplifying
x = 0

See similar equations:

| 5(6y-3)=15y | | 6n+5N= | | x+7=2x+5 | | X^2=66-5x | | 24g-22=2g | | x/3-10=2x | | 0.04(4c-92)=-0.8(c-5) | | -5x-5x=9-4 | | 2/3x=2y-2/5 | | -3(y+3)=-2y+3 | | X^2+5x=16 | | 4x+14-3x=-6-13 | | 12x+9=2x+9 | | X^2-3x-66=0 | | 10x+12=3(3x+2) | | 8x+8+7=5x+12+3x | | 3/2r-7(-17/6r+5/4)=349/4 | | 64X^2Y^3-8X^2=0 | | 8x+16-7x=-2-10 | | -(3x-3)-(10x-6)+8=-4(x-1)-(14x+5)+3 | | 9=-7+1-6 | | -y-5=-9 | | 5(x-8)+x=6(x-8)+8 | | 11x+29y=-13 | | n+7n/5=72 | | 5x+15-4x=-6-12 | | 3/x=13/5x+2 | | 15w^3+14w^2-8w=0 | | -18-6k=6(1+2k) | | 17x=16x-24 | | 7(2x+3)=7 | | 5y+2(y-2)=7y-2(y-10) |

Equations solver categories